Drying and characterization of evaporator concentrates coming from PWR - Érica Rodrigues de Faria; Clédola Cássia Oliveira de Tello (Brazilian Journal of Radiation Sciences, 2021)
In order to control the fission, boric acid is added to the water of primary circuit inside a Pressurized Water Reactor (PWR). After used, this solution is treated in evaporator to reduce its volume, generating the evaporator concentrate (EC). This concentrate should be solidify for transported and storage. Cementation is one of available process to incorporate the concentrate. However, when the evaporator concentrate is cemented there is an increase in the volume of the final product. It is proposed to use an additional process, drying prior be to the cementation. This process is applicable to further reduce the waste volume to be solidificated reducing the number of waste packages, consequently decreasing the storage area and all related risks. Two equipment, lab oven and spray dryer were studied to treat the evaporator concentrate. The dried EC was characterized, and the density, the particle size and the surface area were determined. After drying the evaporator concentrates solution, there was more than 80% weight reduction and initially, the dried product of the spray dryer showed better conditions to be incorporated in cementitious matrix.